PEMANFAATAN SMS UNTUK ALARM PUTUSNYA PASOKAN AIR KOLAM UDANG GALAH BERBASIS MIKROKONTROLER - Djuni Hartawan, Diafari; Agung, Raka; Sukadarmika, Gede (Majalah Ilmiah Teknologi Elektro, 2013)
Pond to enlarge large prawn need continually water flowing to bring water oxygen rich to fulfil requirement large prawn of fresh water and mainly oxygen. SMS or short message service is one another facility of GSM technology that enable to send and receive short message  text form.   SMS sent will be convert previously to PDU code and herewith AT Command is loaded in microcontroller memory. Censors are two copper beams or probe that used to detect water unflowing  from river to pond pass through pipe. If water flowing is interupted transistor switch will connect power supply to microcontroller power supply pin. Microcontroller will send sms to pond owner or keeper HP. SMS sent  are AIR PUTUS X, with X  have value 1 till 5. SMS sent to pond owner HP is done each 10 minutes as much as 5 times. If before 5 times pond owner have arrived at their pond, they can flow water income and resetting their system.  In research, have been producted prototype  to communicate water supply unflowing  at large prawn pond use sms technology be controlled by microcontroller AT89S52.
Keywords: large prawn, water supply, sms, microcontroller